The elements of learning - Banner, James M., Jr., 1935-; Cannon, Harold C., 1930- (Yale University Press, 1999)
Banner and Cannon combine such elements of learning as industry, enthusiasm, pleasure, imagination, and cooperation with circumstances of learning such as who teaches you and how you learn to create a model for the qualities involved in being a student.
Keywords: Learning.; Study skills.; Learning, Psychology of.; College student orientation.; Learning; Apprentissage.; Étude -- Méthodes.; Psychologie de l'apprentissage.; Étudiants -- Orientation.; EDUCATION -- Higher.; College student orientation; Learning, Psychology of; Study skills; Leerstrategieën.; Studievaardigheden.